Analisis Tingkat Kesadaran Keamanan dan Privasi Data di Kalangan Civitas Akademika Menggunakan Model Knowledge-Attitude-Practice - Putu Wida Gunawan; I Gede Pramana Ade Saputra (Infotek: Jurnal Informatika dan Teknologi, 2026)
The rapid digital transformation in higher education increases the risk of data breaches and information security threats. This study analyzes the level of knowledge, attitude, and practice (KAP) regarding data security and privacy among academic community members at Universitas XYZ. A quantitative survey design was employed using a 30-item KAP instrument on a Likert scale, administered in a pilot study to 112 respondents consisting of students, lecturers, and administrative staff. Descriptive analysis shows that knowledge is at a good level (mean = 34.98/50), attitude is very good (mean = 37.39/50), while practice is only at a fair level (mean = 31.30/50). These results indicate that most respondents understand basic concepts of data security and privacy, and have a positive attitude toward protection of personal data, but have not consistently implemented secure digital behaviors in daily activities, such as password rotation, activation of two-factor authentication, and verification of digital signatures. The main finding reveals a significant gap between high attitudes and relatively low security practices, reflecting a privacy paradox in the campus context. The pilot study provides a strong basis to refine the KAP instrument and design a full-scale study to further explore factors influencing digital security behavior in higher education environments